Nitro-oleic acid regulates growth factor-induced differentiation of bone marrow-derived macrophages - Verescakova, Hana; Ambrozova, Gabriela; Kubala, Lukas; Perecko, Tomas; Koudelka, Adolf; Vasicek, Ondrej; Rudolph, Tanja K; Klinke, Anna; Woodcock, Steven R; Freeman, Bruce A; Pekarova, Michaela (Free radical biology & medicine, 2017)
Many diseases accompanied by chronic inflammation are connected with dysregulated activation of macrophage subpopulations. Recently, we reported that nitro-fatty acids (NO2-FAs), products of metabolic and inflammatory reactions of nitric oxide and nitrite, modulate macrophage and other immune cell functions. Bone marrow cell suspensions were isolated from mice and supplemented with macrophage colony-stimulating factor (M-CSF) or granulocyte-macrophage colony-stimulating factor (GM-CSF) in combination with NO2-OA for different times. RAW 264.7 macrophages were used for short-term (1-5min) experiments. We discovered that NO2-OA reduces cell numbers, cell colony formation, and proliferation of macrophages differentiated with colony-stimulating factors (CSFs), all in the absence of toxicity. In a case of GM-CSF-induced bone marrow-derived macrophages (BMMs), NO2-OA acts via downregulation of signal transducer and activator of transcription 5 and extracellular signal-regulated kinase (ERK) activation. In the case of M-CSF-induced BMMs, NO2-OA decreases activation of M-CSFR and activation of related PI3K and ERK. Additionally, NO2-OA also attenuates activation of BMMs. In aggregate, we demonstrate that NO2-OA regulates the process of macrophage differentiation and that NO2-FAs represent a promising therapeutic tool in the treatment of inflammatory pathologies linked with increased accumulation of macrophages in inflamed tissues.
Keywords: MAP Kinase Signaling System; STAT5 Transcription Factor; Cell Differentiation; Inflammation; Signaling pathways; faktory stimulující kolonie; Nitro-oleic acid; Nitro-fatty acids; regulace genové exprese u nádorů; transkripční faktor STAT5; zánět; Oleic Acid; Mice; Phosphatidylinositol 3-Kinases; kyselina olejová; RAW 264.7 buňky; buňky kostní dřeně; fosfatidylinositol-3-kinasy; Macrophages; Extracellular Signal-Regulated MAP Kinases; Growth factors; zvířata; Gene Expression Regulation, Neoplastic; oxid dusnatý; Colony-Stimulating Factors; Bone Marrow Cells; Nitric Oxide; Differentiation; myši; makrofágy; extracelulárním signálem regulované MAP kinasy; RAW 264.7 Cells; MAP kinasový signální systém; buněčná diferenciace; Animals